ChemInform Abstract: Enantioselective Nickel‐Catalyzed Michael Additions of Azaarylacetates and Acetamides to Nitroalkenes. Issue 6 (20th February 2013) - Fallan, Charlene; Lam, Hon Wai
Abstract Azaarylacetamides are reacting with the aromatic nitroalkenes with mostly high diastereoselectivity.